Tailored first-line and second-line CDK4-targeting treatment combinations in mouse models of pancreatic cancer. Issue 12 (28th October 2017) - Chou, Angela; Froio, Danielle; Nagrial, Adnan M; Parkin, Ashleigh; Murphy, Kendelle J; Chin, Venessa T; Wohl, Dalia; Steinmann, Angela; Stark, Rhys; Drury, Alison; Walters, Stacey N; Vennin, Claire; et al.
Abstract : Objective: Extensive molecular heterogeneity of pancreatic ductal adenocarcinoma (PDA), few effective therapies and high mortality make this disease a prime model for advancing development of tailored therapies. The p16-cyclin D-cyclin-dependent kinase 4/6-retinoblastoma (RB) protein (CDK4) pathway, regulator of cell proliferation, is deregulated in PDA. Our aim was to develop a novel personalised treatment strategy for PDA based on targeting CDK4. Design: Sensitivity to potent CDK4/6 inhibitor PD-0332991 (palbociclib) was correlated to protein and genomic data in 19 primary patient-derived PDA lines to identify biomarkers of response. In vivo efficacy of PD-0332991 and combination therapies was determined in subcutaneous, intrasplenic and orthotopic tumour models derived from genome-sequenced patient specimens and genetically engineered model. Mechanistically, monotherapy and combination therapy were investigated in the context of tumour cell and extracellular matrix (ECM) signalling. Prognostic relevance of companion biomarker, RB protein, was evaluated and validated in independent PDA patient cohorts (>500 specimens). Results: Subtype-specific in vivo efficacy of PD-0332991-based therapy was for the first time observed at multiple stages of PDA progression: primary tumour growth, recurrence (second-line therapy) and metastatic setting and may potentially be guided by a simple biomarker (RB protein). PD-0332991 significantly disrupted surrounding ECM organisation, leading to increased quiescence, apoptosis, improved chemosensitivity, decreased invasion, metastatic spread and PDA progression in vivo. RB protein is prevalent in primary operable and metastatic PDA and may present a promising predictive biomarker to guide this therapeutic approach. Conclusion: This study demonstrates the promise of CDK4 inhibition in PDA over standard therapy when applied in a molecular subtype-specific context.